QUALITY ASSURANCE SYSTEM IN HIGHER EDUCATION IN FRANCE - Mospan, Natalia; Durdas, Alla (Continuing Professional Education: Theory and Practice, 2021)
The article presents the quality assurance of higher education in France and reveals the system structure peculiar features. The authors characterize the activity of national agencies for external and internal quality assessment. We show that the formation of French quality assurance in higher education has lasted for three decades. The periodization of the quality assurance shaping in higher education is determined based on reforming the principal national agency for quality. The article illustrates the national legislative documents that regulate external and internal French quality assurance. We believe that a specific feature of the French system of quality assurance in higher education is its subordination to agencies (ENQA and EQAR) at the EU level. The article reveals that the French system of quality assurance in higher education is regulated by legal documents («Standards and recommendations for quality assurance in the EHEA»(ESG)) at the European level; a number of national laws, including the Law on Finance (2001), the Law on Freedom and Responsibility of Universities (2007), the Law on Higher Education and Research (2013); national recommendations and handbooks that form the norms and procedures for assessing the quality of universities. Higher education quality assurance is provided through external assessment and internal self-assessment by universities at the national level. The specificity of the French external quality assessment system’s structure lies in the variety of external agencies and their powers. The High Council for Evaluation in Research and Higher Education (Hcéres) is an independent body. The others external agencies are the Inspectorate General for Public Administration of Education and Training (IGAENR), the Commission of Chartered Engineers (CTI), the Commission for the Evaluation of Management Training and Diplomas (CEFDG) and the Advisory National Commission of University Institutes of Technology (CCN-IUT). National external assessment agencies have a sectoral focus and work in a specific segment, relying on internal quality control procedures. Internal self-assessment is mandatory for all French universities that issue state-recognized diplomas.